2003
DOI: 10.1128/jvi.77.1.159-166.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Uracil DNA Glycosylase Has an Essential Role in DNA Synthesis That Is Independent of Its Glycosylase Activity: Catalytic Site Mutations Reduce Virulence but Not Virus Replication in Cultured Cells

Abstract: Previous findings that the vaccinia virus uracil DNA glycosylase is required for virus DNA replication, coupled with an inability to isolate a mutant with an active site substitution in the glycosylase gene, were surprising, as such enzymes function in DNA repair and bacterial, yeast, and mammalian null mutants are viable. To further study the role of the viral protein, we constructed recombinant vaccinia viruses with single or double mutations (D68N and H181L) in the uracil DNA glycosylase conserved catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 29 publications
(58 reference statements)
3
71
0
Order By: Relevance
“…Interestingly, we also observed that WT and loss-of-catalysis UNG mutants can form a dimer in the cell (Fig. 5 A and B), which raises a possibility that the dimeric structure of UNG could favor a more dynamic scaffolding function, as observed in the case of vaccinia virus UNG (23,24). Future study may reveal how the structure of UNG promotes protein-protein interaction during SHM and CSR at the physiological milieu.…”
Section: Altered Balance Of Repair and Synapse Factors Leads To End-jmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, we also observed that WT and loss-of-catalysis UNG mutants can form a dimer in the cell (Fig. 5 A and B), which raises a possibility that the dimeric structure of UNG could favor a more dynamic scaffolding function, as observed in the case of vaccinia virus UNG (23,24). Future study may reveal how the structure of UNG promotes protein-protein interaction during SHM and CSR at the physiological milieu.…”
Section: Altered Balance Of Repair and Synapse Factors Leads To End-jmentioning
confidence: 86%
“…Curiously, this function of UNG is independent of its catalytic activity. Similarly, vaccinia virus UNG protein, but not its catalytic activity, is essential for the viral replicative cycle by the formation of a large complex to support processive DNA synthesis (23,24). UNG is also known to be recruited to DSB foci in association with γH2AX (25).…”
mentioning
confidence: 99%
“…In contrast, the poxvirus UNG is an obligate component of the replication machinery. Studies performed on D4 (the UNG encoded by vaccinia virus (VACV)) demonstrated that the presence of the protein is crucial for DNA replication as knockout mutants lacking D4 are not viable (14,15), whereas its glycosylase activity is dispensable (16). Later, data obtained from the Traktman group revealed that D4 is a subunit of the VACV DNA polymerase holoenzyme (17).…”
mentioning
confidence: 99%
“…Furthermore, sequence alignments of VACV D4 with related UNGs identified conserved active site residues that are predicted to form the uracil recognition pocket (i.e. Tyr-70, Phe-79, and Asn-120) in addition to Asp-68 and His-181 that are needed for glycosyl bond cleavage (16,21). When the crystal structure of D4 is superimposed onto the human enzyme bound to DNA, these residues match perfectly their human counterparts (20).…”
mentioning
confidence: 99%
“…The vaccinia virus D4R gene, which encodes the viral UNG, is essential for replication in tissue culture, although the catalytic activity is dispensable (14), suggesting that vaccinia virus UNG may participate in the formation of multiprotein DNA replication complexes. Indeed, the interaction of vaccinia virus UNG with A20 (a stoichiometric component of the viral processivity factor), along with E9 (viral DNA polymerase), is necessary and sufficient for the processive polymerase holoenzyme (67).…”
mentioning
confidence: 99%